2022
DOI: 10.1186/s12915-022-01442-9
|View full text |Cite
|
Sign up to set email alerts
|

The Venturia inaequalis effector repertoire is dominated by expanded families with predicted structural similarity, but unrelated sequence, to avirulence proteins from other plant-pathogenic fungi

Abstract: Background Scab, caused by the biotrophic fungus Venturia inaequalis, is the most economically important disease of apples worldwide. During infection, V. inaequalis occupies the subcuticular environment, where it secretes virulence factors, termed effectors, to promote host colonization. Consistent with other plant-pathogenic fungi, many of these effectors are expected to be non-enzymatic proteins, some of which can be recognized by corresponding host resistance proteins to activate plant defe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 177 publications
1
27
1
Order By: Relevance
“…We believe that ancestral origins of many species-specific effector families can be revealed through finer sampling of fungal species. Although MAX effectors were nearly exclusive to M. oryzae in our study, V. inaequalis in Ascomycota was suggested to encode many MAX effector-like proteins 21 . Similarly, Sporisorium reilianum related to U. maydis encodes Tin2-like effectors found exclusively in U. maydis in our study 46 .…”
Section: Finer Species Sampling For Better Evolutionary Resolutioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We believe that ancestral origins of many species-specific effector families can be revealed through finer sampling of fungal species. Although MAX effectors were nearly exclusive to M. oryzae in our study, V. inaequalis in Ascomycota was suggested to encode many MAX effector-like proteins 21 . Similarly, Sporisorium reilianum related to U. maydis encodes Tin2-like effectors found exclusively in U. maydis in our study 46 .…”
Section: Finer Species Sampling For Better Evolutionary Resolutioncontrasting
confidence: 55%
“…lycopersici could be grouped into a few structural families, including Fol dual-domain (FOLD) effector family 8 . In Venturia inaequalis, MAX effectors represented one of the most expanded families 21 . Such structural analyses have reinforced the divergent evolution hypothesis in that pathogen virulence factors may have evolved through frequent duplications and rapid divergence of common folds.…”
Section: Known Virulence Factors Represent New Suss Effector Classesmentioning
confidence: 99%
“…V. inaequalis is an ascomycete fungus, in the Venturiaceae family, responsible for apple scab disease. Assessing models of V. inaequalis MAX-like effectors [45] against the criteria we defined here to assign MAX effectors to subfamilies, revealed that none of the models fitted into any of the MAX subfamilies. Indeed, V. inaequalis MAX effectors present three remarkable disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MAX-like effectors of V. inaequalis usually possess a C-terminal helical extension connected to the MAX core domain via a specific disulfide bond that was not observed in any MAX from P. oryzae . This makes these newly discovered MAX-like effectors from V. inaequalis another subfamily with unique sequence/structure features [45]. As V. inaequalis exclusively colonizes and releases effectors in the subcuticular host environment without penetrating the underlying epidermal cells, their function, and thus targets, are probably fundamentally different from the other studied MAX effectors from P. oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on the biology of MAX effectors have demonstrated how these MAX effectors target host proteins (Bentham et al, 2021;Maidment et al, 2021;Oikawa et al, 2020), how they are detected by the plant immune system (De la De la Concepcion et al, 2021a;Guo et al, 2018;Maqbool et al, 2015;Ortiz et al, 2017), and how this interaction has shaped the evolution of host immunity (Bialas et al, 2021;De la Concepcion et al, 2021b). These studies have led to the first steps in the development of synthetic intracellular immune receptors with bespoke pathogen recognition (Bentham et al, 2022;Cesari et al, 2022;De la Concepcion et al, 2019;Kourelis et al, 2023;Liu et al, 2021;Maidment et al, 2023), a goal long pursued in plant biotechnology (Cadiou et al, 2023;Rodriguez-Moreno et al, 2017;Zdrzałek et al, 2023). Despite this progress, studies addressing functional characterization and experimental determination of non-MAX effectors from M. oryzae have remained somewhat behind in comparison to MAX effectors.…”
Section: Introductionmentioning
confidence: 99%